Detection and transmission of Carrot torrado virus, a novel putative member of the Torradovirus genus - Rozado-Aguirre, Zuriñe; Adams, Ian; Collins, Larissa; Fox, Adrian; Dickinson, Matthew; Boonham, Neil (Elsevier, 2016)
A new Torradovirus tentatively named Carrot torrado virus (CaTV) was an incidental finding following a next generation sequencing study investigating internal vascular necrosis in carrot. The closest related viruses are Lettuce necrotic leaf curl virus (LNLCV) found in the Netherlands in 2011 and Motherwort yellow mottle virus (MYMoV) found in Korea in 2014. Primers for reverse transcriptase-PCR (RT-PCR) and RT-qPCR were designed with the aim of testing for the presence of virus in plant samples collected from the field. Both methods successfully amplified the target from infected samples but not from healthy control samples. The specificity of the CaTV assay was also checked against other known carrot viruses and no cross-reaction was seen. A comparative study between methods showed RT-qPCR was the most reliable method, giving positive results in samples where RT-PCR fails. Evaluation of the Ct values following RT-qPCR and a direct comparison demonstrated this was due to improved sensitivity. The previous published Torradovirus genus specific RT-PCR primers were tested and shown to detect CaTV. Also, virus transmission experiments carried out suggest that unlike other species of the same genus, Carrot torrado virus could be aphid-transmitted.